An analysis in cost efficiency of listed commercial banks in China's first-tier cities and new first-tier cities and its relationship between stock price - Chenzhang, Ruiyu (2019)
This paper estimates the cost efficiency of 30 listed commercial banks in China's tier 1 and new tier 1 cities between 2013 and 2018 and the relationship between the cost efficiency and share price of commercial banks. The Stochastic Frontier Analysis method is used to obtain the cost efficiency results and the regression function form of the relationship between cost efficiency and share price is generated with system Generalized Method of Moments method. The results show that although the cost efficiency increased in 2016, overall there is a decline in cost efficiency from 2013 to 2018. The state-owned commercial banks have better cost efficiency than other kinds of commercial banks. The cost efficiency of commercial banks in tier 1 cities is slightly higher than that of commercial banks in new tier 1 cities. The results of Generalized Method of Moments show that there is an insignificant positive impact of cost efficiency on the share price. Other elements such as asset quality and GDP growth rate have significantly positive effect on the share price.